ALTERNATE USE OF DIFFERENT RICA PROBIOTIC BACTERIA ON SURVIVAL RATE AND PRODUCTION OF CULTURED TIGER SHRIMP IN SEMI-INTENSIVE PONDS - Muharijadi Atmomarsono; Nurbaya Nurbaya (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
Tiger shrimp diseases have occured in Indonesian shrimp ponds for more than two decades. In order to overcome this problem, five types of the RICA probiotic bacteria were tested in nine 250 m2 semi-intensive ponds of the Research and Development Institute for Coastal Aquaculture Marana Station. In the present study three different alternate use of the RICA probiotics were tested for tiger shrimp culture incompletely randomized design experiment. There were three treatments here namely: A) alternate use of probiotic bacteria RICA-1, RICA-2, RICA-3; B) alternate use of probiotic bacteria RICA-4, RICA-5, RICA-3, and C) control (without probiotic bacteria); each treatment were applied in three replications. The results showed that survival rate and production of tiger shrimp in treatment A (55.8% and 14.9 kg/pond) and B (52.7% and 16.7 kg/pond) were significantly better (P<0.05) than those of in control ponds (37.4% and 10.9 kg/pond). However, survival rate and production of tiger shrimp between treatment A and B were not significantly different (P>0.05). The average total bacteria population in the cultured water media of treatment A (4.32 x 104 cfu/mL) and B (5.18 x 104 cfu/mL) were relatively higher than control (1.46 x 104 cfu/mL). However the percentage ratio of Vibrio spp. and total bacteria population in the cultured water media of treatment A and B were relatively lower than control. The lower survival rate and production of tiger shrimp in control (C) compared to probiotic treatments (A and B) were not just affected by the increase of Vibrio spp. ratio, but also affected by the increase of total organic matter and nitrite concentrations in the control ponds that were relatively higher than treatment A and B.